Management of citrus scab caused by Elsinoe fawcettii - and KULDIP SINGH, DALJEET SINGH, S.P. KAPUR (Indian Phytopathology, 2002)
Citrus scab caused by Elsinoe fawcettii is a serious disease of citrus in India. It can cause severe deformation of foliage and stunting of certain citrus rootstocks. This results in poorer quality and smaller caliper of rootstocks for budding. Moreover, premature leaf and fruit drop caused by this malady result in heavy losses to orchardists. Considering the seriousness of the disease in Punjab, the present study was conducted. Blitox-50 (copper oxychloride), Bordeaux mixture, Derosal [carbendazim], chlorothalonil and Indofil M-45 [mancozeb] at 1000 ppm each were tested against the pathogen in in vitro culture resulting in 81.1, 88.0, 77.2, 76.6 and 64.4% growth inhibition of the pathogen over untreated control, respectively. Blitox 50 at 0.3%, Bordeaux mixture at 1%, Derosal at 0.2%, chlorothalonil at 0.2% and Indofil M-45 at 0.3% reduced the disease incidence in the field by 47.8, 69.5, 46.2, 50.4 and 40.4% over control, respectively. Trichoderma viride, T. ressei [T. longibrachiatum] and Epicoccum purpurascens [E. nigrum] showed antibiosis whereas T. harzianum and T. koningii showed mycoparasitism on the pathogen in in vitro culture. T. harzianum and E. purpurascens reduced the disease incidence in the field on spraying by 17.8 and 10%, respectively. Out of 64 citrus species/cultivars screened under natural conditions in the field, 45 were free from infection, 4 tolerant, 7 moderately susceptible, 4 susceptible and 5 highly susceptible with 0, 0-10%, 11-20%, 21-30%, and above 30% disease index, respectively.